Risks and perception of non-communicable diseases and health promotion behavior of middle-aged female immigrants in Japan: a qualitative exploratory study - Yasuko Nagamatsu; Edward Barroga; Yumi Sakyo; Yukari Igarashi; Yuko Hirano O (BMC, 2020)
Abstract Background Ensuring good health of immigrants is a serious issue across countries, including Japan. This study focused on the health of middle-aged female immigrants in Japan who experienced changes to their health as well as an increased risk of non-communicable diseases. Specifically, the study aimed to clarify the risks and perceptions of non-communicable diseases and health promotion behavior of middle-aged female immigrants in Japan. Methods This investigation used an exploratory design. The participants were a purposive sample of 35 middle-aged female immigrants (age ≥ 40 years) living in urban and rural areas of Japan. Data were generated using mixed methods. A quantitative approach provided data of their risks of non-communicable diseases. Focus group discussions provided insights to identify their health promotion perceptions. Results Blood pressure measurement revealed that 29% of the immigrants had hypertension, 29% had a body mass index of > 30, and 71% had an abdominal girth of > 80 cm. About 31% had a history of chronic disease and 34% had regular medication. There were 80% who received regular health check-up, 49% who received breast cancer screening, and 34% who received cervical cancer screening. The focus group discussions indicated that the middle-aged female immigrants recognized the threat of non-communicable diseases. However, they lacked knowledge about the prevention of non-communicable diseases, and they felt that non-communicable diseases were unavoidable. They also failed to understand the benefits of health promotion behavior. The study revealed that the monolingual Japanese health service prevented immigrant women from understanding their health check-up and cancer screening results, and how to utilize the health service system. Conclusions Middle-aged female immigrants in Japan had potential risks of non-communicable diseases, and recognized their threat. These settled immigrant women received health check-ups and cancer screenings with the support of their family, and consequently attained the same level of adherence as that of Japanese women. However, lack of knowledge about health promotion and its benefits and the absence of a culturally sensitive health service system for immigrants in Japan constrained their health-promotion behavior. Sociocultural multilingual-tailored interventions including interpretation services by care providers with cultural sensitivities must be developed.